Autoantibody presentation in drug-induced liver injury and idiopathic autoimmune hepatitis: the influence of human leucocyte antigen alleles. Issue 9 (September 2016) - Stephens, Camilla; Castiella, Agustin; Gomez-Moreno, Eva M.; Otazua, Pedro; López-Nevot, Miguel-Ángel; Zapata, Eva; Ortega-Alonso, Aida; Ruiz-Cabello, Francisco; Medina-Cáliz, Inmaculada; Robles-Díaz, Mercedes; Soriano, German; Roman, Eva; et al.
Abstract : Objectives: Positive autoantibody (AAB) titres are commonly encountered in autoimmune hepatitis (AIH) and in a proportion of drug-induced liver injury (DILI) patients. The underlying mechanism for selective AAB occurrence in DILI is unknown, but could be associated with variations in immune-associated genes. Hence, we aimed to analyse human leucocyte antigen (HLA) allele compositions in DILI with positive (+) and negative (−) AAB titres and in AIH patients. Methods: High-resolution genotyping of HLA class I (A, B, C) and II (DRB1, DQB1) loci was performed on 207 DILI and 50 idiopathic AIH patients and compared with 885 healthy Spanish controls. Results: Compared with controls, HLA-B*08:01 [44 vs. 9.7%, P =3.7E−13/corrected P -value ( P c ) = 1.0E−11], C*07:01 (46 vs. 24%, P =6.4E−04/ P c = 0.012), DRB1*03:01 (58 vs. 21.5%, P =5.0E−09/ P c = 1.0E−07) and DQB1*02:01 (56 vs. 22%, P =6.8E−08/ P c = 9.0E−07) were significantly more frequent in AIH patients. The HLA-A*01:01 frequency was increased in the same population, but did not reach significance after Bonferroni's correction (34 vs. 19%, P= 0.02/ P c = 0.37). Fifty-eight of 207 DILI patients presented positive titres for at least one AAB (predominantly antinuclear antibody 76% and antismooth muscle antibody 28%). There was a tendency towards higher representation of DRB1*14:01 and DQB1*05:03 in DILI AAB+ compared with DILI AAB− (13.8 vs. 4.0%, P= 0.02/ P c = 0.5; 13.8 vs. 4.7%, P= 0.04/ P c = 0.5). Conclusion: The presence of HLA alleles B*08:01, C*07:01, DRB1*03:01, DQB1*02:01 and possibly A*01:01 enhances the risk of AIH (type 1) in Spanish patients. These alleles form part of the ancestral haplotype 8.1. HLA-DRB1*14:01 and DQB1*05:03 could potentially increase the risk of positive AAB (particularly antinuclear antibody) in Spanish DILI patients.